(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Talent management refers to a systematic approach used by organizations to identify, recruit, develop, and retain talented employees. It involves a range of practices such as recruitment and selection, training and development, performance management, career planning, and employee engagement. Effective talent management practices help organizations enhance employee capabilities, improve productivity, and foster a culture of continuous learning and development. In the IT sector, where rapid technological changes require constant skill enhancement, talent management plays a vital role in maintaining workforce competence and organizational performance. Employee performance is one of the key indicators of organizational effectiveness. When employees are properly trained, motivated, and supported through talent management initiatives, they are more likely to perform efficiently and contribute positively to organizational goals. Kanyakumari District has witnessed considerable growth in the IT and IT-enabled services sector in recent years, creating new employment opportunities for skilled professionals. The important objectives of the study are: to examine the talent management practices adopted in IT sector organizations in Kanniyakumari District and to analyze the impact of talent management on employee performance in the IT sector. The study is based on both primary and secondary data sources. In order to examine the impact of talent management on employee performance in the IT sector in Kanniyakumari District, a total of 75 employees working in various IT organizations were selected as respondents for the study. The samples were chosen using the convenience sampling method.